Impact Use of Gadgets Against Growth And Development in Children Aged 2-5 Years at Posyandu Kenanga V Karawang Regency - Ahmad Nawawi, Puji; Rukmaini; Rini Kundaryati (International Journal of Midwifery and Health Sciences, 2025)
Use gadget no only used by adults However child ages 2 – 5 years have also Lots use . Use excessive gadgets​ Of course can influential to growth and development children . Research objectives This aim For know connection intensity use gadgets with growth and development Children aged 2 – 5 years at Posyandu Kenanga V, Dawuan Tengah Village. Methodology design study This use descriptive analytic with approach cross-sectional. Sample in the study This totaling 67 respondents . Retrieval technique sample with use Purposive Sampling. Research instrument consists of from questionnaire use gadgets , growth of BB/U and TB/U use curves and developments child use KPSP measurement . Data analysis using statistical tests Spearman Rho's for know connection intensity use gadgets against growth and development child ages 2 – 5 years at Posyandu Kenanga V, Dawuan Tengah Village. Research results using the Spearman Rho's test to obtain mark rvalue = 0.000 with r value of 0.611 which shows that intensity use influential gadgets to development children , whereas Spearman Rho's test results were obtained mark rvalue = 0.001 and rvalue = 0.002 which shows that intensity use influential gadgets to growth of children's BB/U and TB/U ages 2 – 5 years at Posyandu Kenagan V, Central Dawuan Village. Conclusions obtained from the research This that there is connection intensity use gadgets against growth and development child ages 2 – 5 years at Posyandu Kenanga V, Dawuan Tengah Village. It is hoped that intensity use gadgets for children more attention to growth and development child in accordance with age his.